Development and Validation of a New RP-UFLC Method for the Assay of Binary Mixture of Perindopril Erbumine and Amlodipine Besylate - Annapurna, Mukthinuthalapati Mathrusri (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: Perindopril erbumine is a drug used for the treatment of hypertension which acts by inhibition of angiotensin-converting enzyme. Amlodipine besylate is a calcium channel blocker. A new reversed-phase ultra-fast liquid chromatography method has been developed for the simultaneous determination of perindopril erbumine and amlodipine besylate. Materials and Methods: An ion pairing agent, tetra butyl ammonium hydrogen sulfate (10 mM) with acetonitrile was used as mobile phase (pH to 3.45) (45:55, v/v) on isocratic mode with flow rate 0.8 mL/min (Detection wavelength 215 nm). Results and Discussion: Beer-Lambert’s law was obeyed over the concentration range 0.1–20 μg/mL and 0.25–50 μg/mL with linear regression equation y = 28559x – 1188 (R² = 0.9999) and y = 20401x + 7.07 (R² = 0.9999) for perindopril erbumine and amlodipine besylate, respectively. The limit of quantification values were found to be 0.0912 μg/mL and 0.2123 μg/mL and that of limit of detection values was 0.0291 μg/mL and 0.0691 μg/mL for perindopril erbumine and amlodipine besylate, respectively. The proposed method was validated and found to be simple, precise, accurate, robust, and useful for the routine analysis of pharmaceutical formulations. Conclusion: The proposed method was validated and found to be simple, precise, accurate, robust, and useful for the routine analysis of pharmaceutical formulations.